Compulsory coding in education: liberal-humanism, Baudrillard and the 'problem' of abstraction - Laurence Tamatea (The Asia-Pacific Society for Computers in Education (APSCE), 2019)
Abstract Internationally, coding is increasingly introduced into primary and junior high schools (children generally aged between 5 and 15) on a compulsory basis, though not all stakeholders support this 'initiative'. In response to the public reception, discussion highlights popular argument around compulsory coding in school education. This is an argument between those supportive (hereafter referred to as the Yes case) and those unsupportive of compulsory coding (hereafter referred to as the No case). But more than simply produce a list of arguments, this discussion contributes to our understanding of this reception by identifying the 'discourses' deployed by both cases (namely, digital ubiquity, disadvantage, and habits of mind discourses) and by providing theoretical framings through which these discourses and their potential implications might be differently understood. Using critical discourse analysis to unpack these discourses shows that while both cases hold to key tenets of liberal-humanism, a commitment to the individual subject, liberty and full participation in the social, it is the Yes case with its stronger commitment to children engaging in abstraction that seems to challenge these. Discussion of this difference is framed by the work of Baudrillard around abstraction, not to 'prove' the validity of Baudrillard's thesis concerning the consequences of humanity's deepening engagement with abstraction, but to provide a broader understanding of this debate, in relation to a trajectory of engagement with abstraction that seems set to intensify.